A new hybrid and further taxonomic notes on Brazilian tree ferns (Cyatheaceae) - Schwartsburd, Pedro Bond; Becari-Viana, Ivan; Lopes, Lucas Da Rocha; Lehnert, Marcus (Phytotaxa, 2015)
We here describe a new hybrid within the Cyathea corcovadensis-complex: C. ×stella-matutina (C. corcovadensis s. str. × C. microdonta). We also characterize another two Cyatheaceae species from Brazil: C. mexiae (≡ Trichipteris gardneri), which has been long overlooked, and Alsophila salvinii, an Andine species recently discovered in Brazil. We provide descriptions, illustrations and comments for the three taxa. We also provide a key to the C. corcovadensis-complex, an updated key to species of Alsophila from Brazil, one lectotypification, and anatomical section images of the pinnule articulations of C. ×stella-matutina and its putative parents.